DEVELOPMENT OF A FINANCIAL ANALYSIS TOOL: RISK ASSESSMENT IN THE PROCESS OF STUDYING THE INVESTMENT PROJECTS EFFICIENCY - Efimova, O.V; Koroleva, D.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Investment decisions are made in conditions of uncertainty and risks. Therefore, it is necessary to improve the risk assessment tools in the analysis of the effectiveness of investment projects. In the world practice, a lot of experience has been accumulated in the development and application of models for assessing the effectiveness of investment projects, but not all of them are able to take into account non-financial factors that affect the investment project and represent risks and uncertainties that are important to consider in assessing the effectiveness of an investment project. The importance and relevance of this topic lies in the fact that timely and comprehensive analysis of investments, taking into account the factors of sustainable development, risks and uncertainties in which the organization has to operate, is a fundamental process of strategic activity of the organization and contribute to the increase in the value of the company. A common disadvantage of traditional performance indicators of investment projects is the requirement of certainty of input data, which leads to significantly biased point estimates of performance and risk of the project. The presence of different types of uncertainties leads to the need to adapt the traditional indicators for assessing the economic efficiency of an investment project on the basis of mathematical methods that allow formalizing and simultaneously processing different types of uncertainty. In the conditions of the above uncertainty, the regularizing Bayesian approach can serve as a methodological basis for creating models of complex dynamically developing systems. Its advantages consist in its ability to provide stable estimates and models in conditions of small samples, different types of information, significant inaccuracy of data and fuzzy knowledge about the control system, the control object and the environment. The use of Bayesian intelligent technologies to analyze the effectiveness of the investment project allows to consider in detail the investment project from all possible sides in conditions of significant uncertainty, as well as to assess the probability of occurrence of an event in the project, to show the dispersion of the resulting values, which further contributes to a more informed and deliberate investment decision. The paper presents a model for evaluating the effectiveness of an investment project using intelligent Bayesian networks.